Education Transformation: Innovation of Islamic Learning and Ethics Website for State High School 5 Luwu, South Sulawesi - Ansar, Renita; Hasanuddin, Kartika; Hasanuddin, Kartini (South Sulawesi Education Development (SSED), 2024)
This study aims to identify the need for the development of learning tools at State High School 5 Luwu, especially in the context of Islamic Religious Education, to support learning outside the school environment. Through interviews and observations with teachers, the study highlighted the limitations of teaching media and demonstrated solutions by developing responsive learning tools. The findings emphasize the importance of evaluation and monitoring in learning outside of formal class hours, providing a basis for the development of dynamic and interactive learning solutions. The subject-focused website interface design proves its effectiveness in overcoming student boredom. Black box testing showed positive performance, supporting the website's potential to improve the student learning experience at State High School 5 Luwu